Porting and Enhancing a Mental Health Narrative Game for VR: Redesign Insights and New Features for the Meta Quest Platform - de Oliveira, Thiago Narak C.; Rodrigues, Maria Andréia Formico (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2023: Anais do XXV Simpósio de Realidade Virtual e Aumentada, 2023)
This paper delves into the intricate process of porting and enhancing a mental health narrative game for the Meta Quest 2 virtual reality (VR) platform. We chose Meta Quest 2 due to its unique combination of user accessibility, standalone capability, and highperformance tracking and rendering—traits that align closely with our mental health education and engagement objectives. Our meticulous journey focused on adapting to the platform’s unique capabilities and limitations and innovatively incorporating new features to improve gameplay and enhance mental health awareness. These new features include updated object interactions, the integration of direct VR interactions, an overhauled user interface, and the incorporation of a virtual body to intensify the player’s sense of presence and immersion. Our work offers valuable insights and lessons for future VR game design and development, including performance optimization, aesthetics preservation, comfort and safety considerations, motion sickness prevention, player guidance, 3D tracking, object interaction mechanics, and immersion. Ultimately, these findings provide a roadmap for developers undertaking the challenging task of adapting and enhancing games for VR platforms.